Lack of impact of type and extent of prior therapy on outcomes of mogamulizumab therapy in patients with cutaneous T cell lymphoma in the MAVORIC trial. Issue 13 (10th November 2021) - Horwitz, Steven; Zinzani, Pier Luigi; Bagot, Martine; Kim, Youn H.; Moskowitz, Alison J.; Porcu, Pierluigi; Dwyer, Karen; Sun, Wei; Herr, Fiona M.; Scarisbrick, Julia
Abstract: Patients with mycosis fungoides (MF) and Sézary syndrome (SS) often require multiple lines of systemic therapy. In the phase 3 MAVORIC study (NCT01728805), mogamulizumab demonstrated superiority to vorinostat in median progression-free survival (PFS) and confirmed overall response rate (ORR) in patients with MF/SS. This post hoc analysis examined the effects of number and type of prior systemic therapies on mogamulizumab response. MAVORIC patients randomized to mogamulizumab (1.0 mg/kg intravenously weekly) or vorinostat (400 mg orally daily) were grouped by number of prior therapies and immunomodulatory activity of immediate prior systemic therapy while also considering time elapsed since treatment. ORR, PFS, and duration of response (DOR) did not vary with number of prior therapies. ORR and DOR remained consistent regardless of immediate prior therapy type. Additionally, immunomodulatory activity of the last prior therapy and time from prior treatment generally did not affect the ORR or PFS observed in response to mogamulizumab.